Achievement of Dynamic Equivalence in the Translation of Enola Holmes Movie’s Subtitle - Ummi Mukhoyyaroh; Abdurrachman Faridi (English Education Journal, 2023)
In translation, dynamic equivalence aims to deliver a text’s message in terms that a new recipient audience can understand. This research centered on analyzing the Indonesian translation of the movie subtitles for "Enola Holmes" from English to achieve dynamic equivalence. The main objective was to assess the level of dynamic equivalence and translation quality. The study utilized the content analysis method and employed three instruments: document analysis, a questionnaire, and interviews. The theoretical framework adopted for dynamic equivalence was Nida and Taber's (1964) theory, while the concept of translation quality was based on Nababan et al (2012) work. The findings of the study revealed the following; the accuracy was highly precise, with 78 instances out of 208 data samples. This indicates that the translation effectively conveyed the original meaning without any spelling or grammatical deviations in the use of terms. The acceptability of the translation product was 86.3 instances out of the data analyzed. This suggests that the translation felt natural, employing commonly used and familiar terms that were in line with the rules of Bahasa. Based on readability formula checkers, the translation achieved a very easy readability level suitable for readers aged 8-9 years old, equivalent to 3rd and 4th graders. The study demonstrated a close relationship between accuracy, acceptability, and readability in achieving dynamic equivalence. Furthermore, it is recommended that future researchers focus on specific objects and issues in translation studies.